Sharps Waste and Needlestick Injuries in Healthcare Settings - N Almatrafi, Aminah Rahil; Alzahrani, Khalid Mohammed; Alrasheed, Emad Abdullah; Jarrah, Turki Abdullah; Almaili, Wael Yousef; Almutairi, Thamer Awad; Aldoaibi, Mohammed Saad; Alabdullah, Fares Mohammed; Alsallami, Osama Ali; Fahad Alqahtani, Mohammad; Muhayl Almutairi, Sulaiman (International Journal of Aquatic Research and Environmental Studies, 2026)
Sharps waste is generated wherever needles, lancets, scalpels, suture needles, guidewires, broken glass or other skin-penetrating devices are used. Its management is inseparable from the prevention of needlestick and other sharps injuries because risk persists from the moment a device is handled until the closed container is treated and finally disposed of. This narrative review examines the epidemiology and circumstances of sharps injuries, the contribution of waste-management practices, and the effectiveness of preventive measures in healthcare settings. A focused search of peer-reviewed studies and authoritative guidance published from 1990 to June 2026 was undertaken, with emphasis on surveillance data, Saudi Arabian evidence, intervention studies and current occupational-exposure guidance. Reported injury patterns varied by setting and method of ascertainment, while underreporting was consistently substantial. Nurses, physicians, trainees, surgical personnel, phlebotomy staff and waste handlers faced distinct hazards. Injuries occurred during procedures, recapping, transfer of instruments, disposal, and contact with overfilled or incorrectly segregated containers. Evidence supported a layered prevention strategy combining elimination of unnecessary injections, safety-engineered devices, point-of-use puncture-resistant containers, standardized work practices, training, surveillance and prompt post-exposure management. Device introduction alone was less reliable when activation was difficult or workflow was unchanged. Healthcare organizations should treat sharps safety as a continuous clinical-and-waste pathway, supported by procurement, infection prevention, occupational health and environmental services.
Keywords: sharps waste; needlestick injuries; occupational exposure; healthcare workers; safety-engineered devices; waste management